Efecto del extracto acuoso de ajo (allium sativum l) sobre parámetros productivos en la cría de pollos cobb 500 - Briones Loor, Sophía (2018)
In Portoviejo country, Manabi province a study was conducted to observe the behavior of aquous garlic extract in the drinking water of Cobb 500 chickens under certain sanitary and productive variables, at the rate of 0.05%, 0.5%, 1% y 3% of daily food consumption (Cobb 500 table) denominated T1, T2, T3, and T4 respectively, and a control group T0. A total of 245 birds were used and randomly distributed between 7 observational units (chickens) and within 35 experimental units. The results of the investigation were processed in the Infostat statistical package (2015) for the median distribution with 95% confidence level. The T4 treatment group was the one with the highest cumulative weight gain and consumption with 2668 g and 5702 g respectively. While T1 obtained the best food conversión 2.03 at 49 days old, however within the parameters mentioned above, no significant difference was found (p>0.05). A significant difference was found (p<0.05) at 38 days old in the mean corpuscular hemoglobin concentration (MCHC), being greater T3 with 58.99 g/dl of blood. No significative difference was observed (p>0.05) between morphometric indexes of Bursa and Thymus at 49 days old. It is concluded that the use of aqueous garlic extract does not affect significantly (p>0.05) on productive parameters.